The Food Safety Modernization Act of 2011 – Proposed Rule for Preventive Controls for Human Food - Soohyoun Ahn; Keith R. Schneider; Michelle D. Danyluk; Renee Goodrich-Schneider (EDIS)
The Food Safety Modernization Act (FSMA), which was signed into law by President Obama on January 4, 2011, is the most sweeping reform of food safety laws in more than 70 years since the enactment of the Federal Food, Drug and Cosmetic Act of 1938. High-profile foodborne outbreaks in the last decade and their impact on public health and the economy have exposed the need for a new, modern food safety system. FSMA aims to ensure the safety and security of the US food supply by focusing on preventing food safety problems rather than responding after they occur. This law provides the FDA with new enforcement authorities to achieve a higher rate of compliance with food safety standards and to respond better to problems. This 5-page fact sheet was written by Soohyoun Ahn, Keith R. Schneider, Michelle D. Danyluk, and Renee Goodrich-Schneider, and published by the UF Department of Food Science and Human Nutrition, April 2014.